2018
DOI: 10.3892/or.2018.6673
|View full text |Cite
|
Sign up to set email alerts
|

Dermcidin as a novel binding protein of lncRNA STCAT3 and its effect on prognosis in gastric cancer

Abstract: Long non‑coding RNAs (lncRNAs) perform distinct biological functions by regulating gene expression through various molecular mechanisms under normal physiological and pathological conditions. However, the function of the stomach cancer‑associated transcript‑3 (STCAT3) lncRNA, including its prognostic significance and role as a binding protein in gastric cancer (GC), remain unclear. In the present study, 56 potential binding proteins of STCAT3 were screened using through mass spectrometry and bioinformatics ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…DCD is a protein with antimicrobial activity and displays phosphatase activity (Zhang et al, 2018). Its higher abundance is associated with tumor progression (Stewart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…DCD is a protein with antimicrobial activity and displays phosphatase activity (Zhang et al, 2018). Its higher abundance is associated with tumor progression (Stewart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Initial evidence reported by Porter et al revealed that the protein was overexpressed in 10% of invasive breast carcinomas and conferred cell growth and survival, launching dermcidin as a candidate oncogene [ 51 ]. Thereafter, several research groups reported additional evidence concerning this protein in various types of cancers, as illustrated in Figure 7 : Intracellular or extracellular overexpression of dermcidin in breast cancer [ 52 ], gastric cancer [ 53 , 54 ], hepatocellular carcinoma [ 55 , 56 ], lung cancer [ 57 , 58 ], melanoma [ 59 , 60 ], and pancreatic cancer [ 61 ]; promotion of cell survival [ 48 , 51 , 62 , 63 , 64 ]; and promotion of cell migration [ 55 , 65 ]. Although there are solid data that link dermcidin and cancer, the proper role of the protein at molecular levels and its contribution to tumorigenesis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Serum dermcidin levels were significantly increased in hepatocellular carcinoma patients and were positively correlated with metastasis [25]. Dermcidin expression in gastric cancer reflects overall survival and is positively correlated with lymph node metastasis [20]. Dermcidin expression is higher in lung cancer patients compared with that in healthy subjects [26].…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons behind this might be that dermcidin contributes to the development of the tumor. High dermcidin expression is associated with tumor growth in gastric [20] and breast cancer [21]. Interestingly, dermcidin is also associated with tumor growth and tumor apoptosis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%